2018
DOI: 10.1039/c8gc00200b
|View full text |Cite
|
Sign up to set email alerts
|

Microplasma-assisted electrochemical synthesis of Co3O4nanoparticles in absolute ethanol for energy applications

Abstract: The anodisation of Co foil in an absolute ethanol electrolyte with a microplasma cathode produces size-controllable Co3O4 quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 70 publications
3
25
0
Order By: Relevance
“…A microplasma‐liquid method was designed to synthesize cuprous oxide (Cu 2 O) NPs with the size ranging from 400 to 600 nm . It was further demonstrated that crystalline Co 3 O 4 NPs with the diameters 2–5 nm can be fabricated by using Co foil as the anode in the microplasma‐enhanced electrochemical reactor operated at ambient conditions . The Co 3 O 4 NPs produced in this method can be dispersed in ethanol and then used to fabricate thin films for light absorption and light‐emitting diode applications.…”
Section: Production Of Advanced Nanomaterialsmentioning
confidence: 99%
“…A microplasma‐liquid method was designed to synthesize cuprous oxide (Cu 2 O) NPs with the size ranging from 400 to 600 nm . It was further demonstrated that crystalline Co 3 O 4 NPs with the diameters 2–5 nm can be fabricated by using Co foil as the anode in the microplasma‐enhanced electrochemical reactor operated at ambient conditions . The Co 3 O 4 NPs produced in this method can be dispersed in ethanol and then used to fabricate thin films for light absorption and light‐emitting diode applications.…”
Section: Production Of Advanced Nanomaterialsmentioning
confidence: 99%
“…The synthesis of CoPt 3 , CoPt, SmCo NPs can also be carried out using the same method. A recent work by the Mariotti group also proved that Co 3 O 4 NPs can also be obtained by microplasma discharged in absolute ethanol [94].…”
Section: Application Of Plasma For the Synthesis And Modification mentioning
confidence: 99%
“…With an improved theoretical understanding and a broader range of the available data this study is also well motivated by the need to produce a basis for a more comprehensive data set for pertinent processes and by the need to address possible applications (as listed here) by detailed modelling. This paper is an attempt to extend the existing studies in alcohol vapours (see [24,[38][39][40][41][42][43]) with careful and well-defined procedure to measure the observables from the discharges in order to obtain some data on primary and secondary processes in a subsequent analysis. The Paschen curve for discharge in methanol vapour have been presented in our earlier paper [18] while V-i characteristics for pd=0.15 and 0.40 Torr cm are shown in present paper in figure 3.…”
Section: Introductionmentioning
confidence: 99%